BEYKER-KEMPBEL-XAUZDORF FORMULASIGA OID BIR MASALANING YECHILISH METODIKALARI - Yavidov, B.; Saburova, G.; Nurimbetov, K.; Ollomberganova, M. (SCIENCE and SOCIETY, 2020)
In the article a particular problem, connected with Baker-Campbell-Hausdorff formula, is considered. It is duscussed how the problem is considered in textbooks. Three methods of solution of the problem are presented. It is stated that solving problems by different methods in practical classes serves to improve the quality of classes and the practical competence of students.
Keywords: operator; commutator; Baker-Campbell-Hausdorff formula; methods for solving problems